2015
DOI: 10.1007/s40819-015-0054-6
|View full text |Cite
|
Sign up to set email alerts
|

Local Fractional Derivatives of Differentiable Functions are Integer-order Derivatives or Zero

Vasily E. Tarasov

Abstract: In this paper we prove that local fractional derivatives of differentiable functions are integer-order derivative or zero operator. We demonstrate that the local fractional derivatives are limits of the left-sided Caputo fractional derivatives. The Caputo derivative of fractional order α of function f (x) is defined as a fractional integration of order n − α of the derivative f (n) (x) of integer order n. The requirement of the existence of integer-order derivatives allows us to conclude that the local fractio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
(55 reference statements)
0
11
1
1
Order By: Relevance
“…The conditions for applicability of the K-G fractional derivative were not specified in the seminal paper, which leaves space for different interpretations and sometimes confusions. For example, recently Tarasov claimed that local fractional derivatives of fractional order vanish everywhere [36]. In contrast, the results presented here demonstrate that local fractional derivatives vanish only if they are continuous.…”
Section: Discussioncontrasting
confidence: 69%
“…The conditions for applicability of the K-G fractional derivative were not specified in the seminal paper, which leaves space for different interpretations and sometimes confusions. For example, recently Tarasov claimed that local fractional derivatives of fractional order vanish everywhere [36]. In contrast, the results presented here demonstrate that local fractional derivatives vanish only if they are continuous.…”
Section: Discussioncontrasting
confidence: 69%
“…250ff), nonconformable local-type fractional derivative [6]. However, after Tarasov's argument for the principle of nonlocality, attempts to found a fractional calculus on local operator now seriously require a theoretical rigor to avoid becoming objectionable [23,24]. In particular, Abdelhakim [1] has shown that conformable fractional derivative is in fact integer-order derivative in fractional disguise, thereby advising the fractional calculus researchers against its use.…”
Section: The Case Of Caputomentioning
confidence: 99%
“…cannot hold for fractional derivatives of order α = 1 for sets of differentiable and non-differentiable functions [19,20,21,22]. Unusual properties of fractional derivatives of non-integer orders that are represented by deformations a of the usual Leibniz rule, and the usual chain rule can be considered as the characteristic properties of fractional-order derivatives.…”
Section: Accepted Manuscriptmentioning
confidence: 99%